Relative systolic blood pressure reduction and clinical outcomes in hyperacute intracerebral hemorrhage. Issue 5 (May 2015) - Sakamoto, Yuki; Koga, Masatoshi; Todo, Kenichi; Okuda, Satoshi; Okada, Yasushi; Kimura, Kazumi; Shiokawa, Yoshiaki; Kamiyama, Kenji; Furui, Eisuke; Hasegawa, Yasuhiro; Kario, Kazuomi; Okata, Takuya; et al.
<x xml:space="preserve">Abstract</x> Background and purpose: Blood pressure lowering is often performed as a part of general acute management in acute intracerebral hemorrhage (ICH) patients. The relationship between relative blood pressure reduction and clinical outcomes is not fully known. Methods: Hyperacute (<3 h from onset) ICH patients with initial SBP more than 180 mmHg were included in the observational study. All patients received intravenous antihypertensive treatment based on a predefined protocol to lower and maintain SBP between 120 and 160 mmHg. The relative SBP reduction was defined as the ratio of SBP reduction to the admission SBP in the first 24 h, and associations between the relative SBP reduction and neurological deterioration (≥2 points decrease in the Glasgow Coma Scale score or ≥4 increase in the National Institutes of Health Stroke Scale score), hematoma expansion (>33% increase), and unfavorable outcome (modified Rankin scale score 4–6 at 3 months) were assessed with multivariate logistic regression analyses. Results: Of the 211 patients [81 women, median age 65 (interquartile range 58–74) years, and median initial National Institutes of Health Stroke Scale score 13 (8–17)] enrolled, 17 (8%) showed neurological deterioration, 36 (17%) showed hematoma expansion, and 87 (41%) had an unfavorable outcome. On multivariate regression analyses, relative SBP reduction was independently and inversely associated with neurological deterioration (odds ratio 0.053, 95% confidence interval 0.011–0.254 per 10% increment), hematoma expansion (0.289, 0.099–0.841), and unfavorable outcome (0.254, 0.095–0.680) after adjusting for known predictive factors. Conclusion: Insufficient relative SBP reduction after standardized antihypertensive therapy in hyperacute ICH was independently associated with poor clinical outcomes. Aggressive antihypertensive treatment may improve clinical outcomes.